Nitrous oxide and methane in two tropical estuaries in a peatdominated region of North-western Borneo - Aazani, Mujahid; Müller, D.; Warneke, T.; Rixen, T.; Müller, M.; Notholt, J. (Copernicus GmbH (Copernicus Publications)., 2016)
Estuaries are sources of nitrous oxide (N2O) and methane (CH4) to the atmosphere. However, our present knowledge of N2O and CH4 emissions from estuaries in the tropics is very limited because data is scarce. In this study, we present first measurements of dissolved N2O and CH4 from two estuaries in a peat-dominated region of north-western Borneo. Two campaigns (during the dry season in June 2013 and during the wet season in March 2014) were conducted in the estuaries of the rivers Lupar and Saribas. Median N2O concentrations ranged between 7.2 and 12.3 5 nmol L-1 and were higher in the marine end-member (13.0 ± 7.0 nmol L-1). CH4 concentrations were low in the coastal ocean 3.6 ± 0.2 nmol L- 1) and higher in the estuaries (medians between 12.2 and 64.0 nmol L-1). The respiration of bundant organic matter and presumably anthropogenic input caused a slight eutrophication, which did not lead to hypoxia or enhanced N2O concentrations, however. generally, N2O concentrations were not related to dissolved inorganic nitrogen concentrations. 10 Thus, the use of an emission factor for the calculation of N2O emissions from the inorganic nitrogen load leads to an overestimation of the flux from the Lupar and Saribas estuaries. N2O was negatively orrelated with salinity during the dry season, which suggests a riverine source. In contrast, N2O concentrations during the wet season were not correlated with salinity but locally enhanced within the estuaries, implying that there were additional estuarine sources during the wet (i.e. monsoon) season. Estuarine CH4 distributions were not driven by freshwater input but rather by tidal variations. Both N2O 15 and CH4 concentrations were more variable during the wet season. We infer that the wet season dominates the variability of the N2O and CH4 concentrations and subsequent emissions from tropical estuaries. Thus, we speculate that any changes the Southeast Asian monsoon system will lead to changes in the N2O and CH4 emissions from these systems. We also suggest that the ongoing cultivation of peat soil in Borneo is likely to increase N2O emissions from these estuaries, while the effect on CH4 remains uncertain